Improving students’ critical thinking abilities and environmental sensitivity through project-based learning integrated with green chemistry principles - Jusniar, Jusniar; Auliah, Army; Syamsidah, Syamsidah; Fadly, Dewiyanti (Eclética Química, 2025)
This quasi-experimental research seeks to examine the impact of the Project-Based Learning (PBL) model integrated with Green Chemistry (GC) on students’ critical thinking abilities (CTA) and environmental sensitivity (ES) at chemical equilibrium. A Randomized Post-test-Only Control Group design was used in four classes of Class XI F students at SMAN 1 Gowa, South Sulawesi as the population. The samples were classes XI F1 and XI F4, each consisting of 36 students, taken randomly. CTA data was obtained with seven essay questions which have been tested with quite high reliability (0.68). The ES questionnaire consists of 25 statements. Testing with the Independent Sample t-test shows that the integrated PBL GC Model influences increasing student CTA. The Wilcoxon test results also show that the application of the GC-integrated PBL model affects increasing students’ ES. This research implies that it is hoped that teachers will continue to integrate green chemistry in learning continuously to support sustainability programs.